The Readiness to Implement the University Social Responsibility: A Case Study at a Private Indonesian University - Jessica Angel Priscillia; Jurica Lucyanda; Anggita Putri; Sarah Novita Asa (Asia Pacific Journal of Management and Education (APJME), 2025)
This study investigates the readiness to implement the concept of University Social Responsibility (USR) at Bakrie University. USR is a concept of university commitment to the social community through an ethical approach that focuses on a Triple Bottom Line (TBL) approach (environmental, social, and economic). It supports the Civitas Academica in carrying out the work. It is concerned with community service activities from economic, social, and ecological aspects through the Tridarma of Higher Education (education, research, and community service). This study adopts a qualitative method using a case study approach at Bakrie University. The data collection is done through in-depth interviews. The results show that Bakrie University has partially adopted the USR concept. Bakrie University's main challenge in implementing the USR concept is the lack of integration of environmental education in the curriculum and monitoring and evaluating the impact of the USR program. However, the study concludes that Bakrie University is ready to implement USR concepts by focusing on environmental and social-based curriculum design, developing student participation in sustainable activities, and increasing collaboration with industries that focus on sustainability. This study contributes to education and sustainability research, particularly in USR.